2018
DOI: 10.1371/journal.pone.0194289
|View full text |Cite
|
Sign up to set email alerts
|

A new scheme for strain typing of methicillin-resistant Staphylococcus aureus on the basis of matrix-assisted laser desorption ionization time-of-flight mass spectrometry by using machine learning approach

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA), one of the most important clinical pathogens, conducts an increasing number of morbidity and mortality in the world. Rapid and accurate strain typing of bacteria would facilitate epidemiological investigation and infection control in near real time. Matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) mass spectrometry is a rapid and cost-effective tool for presumptive strain typing. To develop robust method for strain typing based on MALDI-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 38 publications
2
67
0
Order By: Relevance
“…1416 On the basis of the massive data produced by MALDI-TOF MS, moreover, some studies have demonstrated that subspecies typing could be predicted from a specific pattern of MS spectra only. 17,19 Furthermore, other studies have shown a good correlation between AST and specific patterns of MS spectra. 18,2325,48 However, some issues have limited the generalization of these results.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…1416 On the basis of the massive data produced by MALDI-TOF MS, moreover, some studies have demonstrated that subspecies typing could be predicted from a specific pattern of MS spectra only. 17,19 Furthermore, other studies have shown a good correlation between AST and specific patterns of MS spectra. 18,2325,48 However, some issues have limited the generalization of these results.…”
Section: Discussionmentioning
confidence: 87%
“…A log score (generated through Biotyper 3.1) larger than 2 was used for confirming E. faecium . 1719 We tested vancomycin susceptibility of E. faecium by using the paper disc method. The details of E. faecium identification and AST are given in the eMethods in the Supplement.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations